Balancing Modernity and Tradition in Neighborhood Attachment and Improvement Preference- Sulaimani Heights in Iraq as a Case Study (Journal of Engineering, 2025)
This study examines residents’ perceptions, attachments, and preferences for neighborhood improvements in Sulaimani, Iraq, a city undergoing rapid urban transformation. The research aims to address two key objectives: (1) To investigate how residents perceive and attach to their old and current neighborhoods; (2) To explore what are their priorities for neighborhood improvements. Using the TwoStep Cluster model in IBM SPSS Modeler, residents were grouped based on their satisfaction with their neighborhoods and their priorities for architectural and infrastructure enhancements. The findings indicate a dual focus: while residents appreciate modern amenities, such as energy-efficient designs and improved public spaces, they also place high value on cultural heritage and social connections. The study further highlights variations in preferences for mixed-use developments and specific infrastructure improvements. These insights emphasize the challenge of balancing modernization with preserving traditional neighborhood identities. The results provide practical recommendations for urban planners and policymakers in shaping sustainable and culturally responsive urban development in Sulaimani and similar contexts.